Mutual stabilization of charge-density-wave and monoclinic distortion in sulfur at high pressures - Owen Moulding; Lewis J. Conway; Israel Osmond; Sam Cross; Andreas Hermann; Jonathan Buhot; Sven Friedemann (Physical Review Research)
The charge-density-wave (CDW) amplitude mode of the high-pressure sulfur-IV phase is observed between 83 and 146 GPa using Raman spectroscopy. The energy of this excitation softens with pressure yet remains finite at ν_{CDW}>100cm^{−1} up to the critical pressure, which is indicative of a weakly first-order transition. Our ab initio calculations show that the finite energy of the excitation originates from the coupling and mutual stabilization of the CDW modulation and a monoclinic lattice distortion. At the critical pressure, both the CDW modulation and lattice distortion disappear simultaneously. Due to the prevalence of CDW phases, this coupling between the CDW modulation and lattice distortion is expected to be relevant for a wide variety of elements and compounds.